Micro/nanosized ferrite and hexaferrite structures: The polyol processes for synthesis - Nguyen Viet Long; Nguyen Thi Nhat Hang; Ho Van Cuu (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2023)
In this research, controlled synthesis and properties of micro/nano-sized magnetic oxide powders via a polyol process are discussed. They are the original magnetic oxides that have been studied by many scholars because of their many applications. The most special forms are the diversity of FeO and Fe2O3, and the diversity of the Fe3O4 matrix which are the most important original structures with formulas to be FeO.Fe2O3 (Fe3O4) and Fe2O3 can be oxide systems of FexOy that are very common and different. On the basis of the original structures, we can synthesize the most special forms of ferrite and hexaferrite related to the four original structures, which are AB2O4-spinel-type SrFe2O4 and BaFe2O4 ferrites (M: metal elements, Sr, Ba; B: Fe), PbFe11AlO19-type MX12O19 (M: metal elements, Sr, Ba; X: Fe) SrFe12O19 and BaFe12O19 by polyol processes and technologies. We understand that elements that form original structures are incorporated into Fe3O4 to form ferrite and hexaferrite structures, typically such as SrFe12O19 by liquid-, solid- and gas-based phase chemical reactions via the polyol processes and heat treatment processes. In the future, we suggest that the original oxide structure and formula of natural minerals can be used as the new magnetic structures and compounds.